O estágio obrigatório como instrumento de inserção no mercado de trabalho - Polzin, Fernanda Ribeiro (2019)
The internship is considered an important didactic-pedagogical tool, which helps the students-trainees approach the job market which they intend to follow. In this way, understanding their agents and knowing the perception of the parties involved contributes to the process of student training. The general objective was to analyze the role of the compulsory traineeship in the training of undergraduate students of the UTFPR Guarapuava campus, based on the perception of the PRAEs and the granting companies, trying to describe the relationship of the learning process with the perspectives of the labor market. The methodology used was documentary research, direct documentary research to the sectors responsible for the internship administration (Coordination of Human Resources Management - COGERH and DIREC), the non-participant observation of the researcher, direct interview with the four Teachers Responsible for the Internship (PRAEs) and the measurement of the perception and satisfaction of the 66 internship grantors through an online questionnaire. Based on the information collected, it was possible to carry out a study about the effectiveness of the internship practice, as well as its importance in the insertion of young people into the labor market. It presents the characteristics of the compulsory stage modality, the result of the questionnaire applied, and interviews conducted with the agents belonging to the process, as well as the main data collected and their respective analyzes. As a result of this study, the importance of DIREC's performance in the internship process, the need to intensify the on-site visits of the PRAEs in the granting units, the lack of official records of post-trainee students' experience, and the positive perception companies have in relation to students. The study enables the reader to reflect about compulsory internship, the University's performance in the students' training process, as well as positive and negative notes regarding the students and the University and company relationship.